(untitled) (Fiep Bulletin - online, 2013)
This study aimed to identify the nutritional profile, eating habits and physical activity of school children aged 8 to 10 years comparing the sexes. The study was transversal, descriptive and quantitative. The population consisted of students who were 55 children of both sexes aged 8 to 10 years. We used a modified lifestyle questionnaire of Barros and Nahas (2003), which evaluated the physical activity level of children and identified their eating habits. To the completion of this work, a descriptive analysis and the Mann-Whitney "t" test to detect differences between the sexes were done using the SPSS 11.0 software. It was found that 46.42% of children were overweight and 53.58% were with an acceptable weight. As for eating habits it was found that 72% have insufficient, 23% adequate and 5% excessive eating. The time spent by children outside of school is spent as follows: 43% play sports, 21% watch TV, 18% play and 18% help at home. As for the level of physical activity, 21.9% of female students are active against 45.8% of male students. Concerning children with sedentary behavior, girls are 28.1% and 20.8% boys. It was concluded that overweight has reached almost 50% of school children who in general are active, as for food consumption, 72% of the children had insufficient eating and most children spend their time outside of school practicing sport.